Schwarzschild anti-de sitter black holes and spacetime atoms :a heuristic approach (2018)
In this work, both extended phase space and holographic equipartition approaches are studied and employed to develop an exact Van der Waals description of nonrotating D = 4 SAdS black holes as an ensemble of spacetime atoms. After a possible micro- scopical interaction model is introduced, statistical mechanics techniques, with certain heuristic gravitational constraints, are used to derive the equation of state and the BekensteinHawking entropy. The procedure is generalized to the charged D = 4 SAdS black hole and to arbitrary D greater than or equal to 3 dimensions for the uncharged cases.